Association between triglyceride glucose index and coronary artery disease with type 2 diabetes mellitus in middle-aged and elderly people. Issue 9 (5th March 2021) - Si, Yueqiao; Fan, Wenjun; Shan, Weichao; Zhang, Ying; Liu, Jingyi; Han, Chao; Sun, Lixian
Abstract : Abstract: This study aimed to investigate the correlation between triglyceride glucose (TyG) index and coronary artery disease (CAD) with type 2 diabetes mellitus (T2DM) and identify the risk associated TyG index in different subgroups. A total of 1665 eligible inpatients (CAD with T2DM group [n = 680], non-coronary artery disease without T2DM [n = 985]) were consecutively enrolled in this study. They were assigned into 4 subgroups: middle-aged, elderly, male, and female subgroups. Receiver operating characteristic curve diagnostic test and a logistic regression model was established to analyze the risk factors for CAD with T2DM. TyG index is an independent risk factor for patients with CAD with T2DM. The risk of increased TyG index is greater in the middle-aged and male subgroups than in the elderly and female subgroups, respectively (all P  < .05). The specificity and the positive predictive value of the TyG index is greater than the sensitivity and the negative predictive value, respectively (all P  < .05). Increased TyG index is a new independent risk factor for CAD with T2DM, and its risk is higher in the middle-aged and male subgroups than in the elderly and female subgroups, respectively. TyG index may be used as a clinical predictor of CAD with T2DM.